Prediction of the impact of logging activities on forest cover: a case study in East province of Cameroon - Mertens, B.; Forni, E.; Lambin, E.F. (2001)
Geographic information system techniques were used in combination with remote sensing data to define the net commercial value of standing timber at two sites (Batouri and Bertoua) in the East province of Cameroon. Observed forest cover modifications for the two sites were assessed in relation to the commercial accessibility of the forest areas. Results showed that, in one site, half of the very high rent areas have already been logged indicating that the unlogged high rent area is scarce and the low rent or marginal forest area remains largely unlogged. However, this was not the case throughout the study area as shown by the observations at the other site. The two main species exploited were sapelli (Entandrophragma cylindricum) and Ayous Triplochiton scleroxylon.